(untitled) (Bangladesh Journal of Child Health, 2025)
Familial adenomatous polyposis (FAP) is characterized by the development of up to hundreds or thousands of adenomas in the colon and rectum with several extra colonic manifestations. These syndromes have multiple genetic characteristics and are associated with an increased risk of colon cancer. An 8-year-old boy presented to our department with a history of repeated episodes rectal bleeding requiring blood transfusion for last 3 month. His laboratory evaluation showed normal hematological parameter. He had multiple polyps on endoscopic examination with histopathological confirmation of adenoma. As genetic testing is not possible in our country, on the basis of clinical presentation and histopathological confirmation he was diagnosed as a case of Familial adenomatous polyposis (FAP). Though Familial adenomatous polyposis (FAP) is the most common type of polyposis in children, it is very rare in our country. BANGLADESH J CHILD HEALTH 2023; VOL 47 (3) : 174-177